2001
DOI: 10.1159/000053758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the H<sub>1</sub>-Receptor Antagonist Cetirizine on the Stimulated Expression of Adhesion Molecules and the Activation of NFκB in Human Endothelial Cells

Abstract: Background: In the present work, we studied the effect of cetirizine on the cytokine-stimulated immune response of human umbilical vein endothelial cells (HUVECs). Methods: Our research was directed to analyze the effect of preincubation of HUVECs with cetirizine (1 µg/ml) on (1) the TNFα-, IL-4- and IFNγ-induced surface expression of ICAM-1 and VCAM-1, (2) the secretion of IL-6 and IL-8, (3) the recruitment of NFĸB and AP-1 and (4) the adhesion of histiocytic monocytes (U937) to activated endothelial monolaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several H1 receptor antagonists have demonstrated inhibitory properties on the production and expression of interleukins, chemokines, and other cytokines [ 33 ]. Specifically, cetirizine decreases interleukin production [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several H1 receptor antagonists have demonstrated inhibitory properties on the production and expression of interleukins, chemokines, and other cytokines [ 33 ]. Specifically, cetirizine decreases interleukin production [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, cetirizine decreases interleukin production [ 60 ]. Antihistamines, apart from their classical action for blocking H1 and H2 receptors, have been identified, recently, as having powerful antiviral properties and inhibit the entry of certain viruses into the target cell [ 61 , 62 ]. In a recent report, it was shown that treatment with antihistamines, plus azithromycin in selected cases, may treat COVID-19 and prevent progression to severe disease in elderly patients [ 63 ].…”
Section: Antihistamines Anti-iges Bronchial Asthma and Covid-1mentioning
confidence: 99%
“…This suggests that antihistamines may help in the treatment of a COVID-19 cytokine storm through their immunomodulatory properties [ 6 , 12 ]. Specifically, cetirizine decreases interleukin production [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%